Development of a Design for Implementation Learning of Oriented on CTL Model to News Writing During the COVID-19 Pandemic - Wismanto, Agus; Samsi, Kastam (KnE Social Sciences, 2022)
News writing – a crucial part of journalism – is a necessity for students, especially those at PBSI (Indonesian Language and Literature Education). Students must be able to produce writings containing news or events that are observed and experienced directly in society. In achieving these output targets, lecturers must be able to motivate students for learning by making it interesting and using the right combination of learning media, learning strategies, and learning models. In this article, the authors discuss how to develop an RPS for news writing using the CTL learning model. The research type is an R&D with development steps according to Sugiyono and Pengembangan. However, the current article describes only the product design process. The study data were collected through discussions of concepts based on various related theories. Keywords: development, model, learning, contextual, COVID-19